LA GERENCIA DEL CONOCIMIENTO COMO FUENTE DE VENTAJA PARA DESARROLLAR LAS MYPES - Tito Huamaní, Pedro (2007)
The results of the investigation demonstrate that the Management of the Knowledge is an innovative and creative administration model for the managerial organizations: micro, small, medium and big companies. Contrary to the last ones, in the first ones (micro and small companies or Mypes), given the financial and administrative limitations for this models´ implementation, the trend should be continued to the personification; it is worth to say, an administration characterized by the permanent contact with their collaborators, in which the technology would help to communicate its knowledge and not only to store them. At internal level, the conditions are not still given - labor climate in the shops and the proprietors’ academic formation – to manage the Mypes on the base of the knowledge accumulated through their collaborators. This is reflected in the zeal that subsists still among the workers, hindering to share knowledge, abilities and dexterities; although they are convinced they have to interact and exchange information to develop the organization. In the same way, starting from the results of the investigation, it is concluded that the acquisition of new knowledge to develop its work has a high value between the workers and proprietors of the MYPEs. We believe this aspect is important to internalize the human interaction values and the team work.